Alexander Gardner manuscript - Gardner, Alexander, 1821-1882.
Volume containing a preface and text for battlefield photographs taken primarily by Gardner, official photographer at Headquarters of the Army of the Potomac, following the battle of Gettysburg, Pa., July 1-3, 1863, and for photographs of the commanding officers taken by Mathew B. Brady and others, 1861-1865. The photographs intended for publication in the volume are not available at the Library of Congress.
Photographer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Brady, Mathew B., -- approximately 1823-1896.; United States. -- Army -- Officers -- Portraits; United States. -- Army of the Potomac; Gettysburg, Battle of, Gettysburg, Pa., 1863.; Pennsylvania -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Campaigns; United States -- History -- Civil War, 1861-1865 -- Photography; Photographers